Control of stomatal aperture and carbon uptake by deficit irrigation in two grapevine cultivars - Souza, Cláudia R. de (2005)
odels for the Mediterranean region. In recent years, deficit irrigation, including partial root drying (PRD), has been proposed as an irrigation technique to improve water use efficiency and standardize grapevine yield and quality. The objective of this study was to evaluate the impact of deficit irrigation on photosynthetic responses of field grown grapevines of cv. Moscatel and Castela˜o. The treatments were: full irrigation (FI), corresponding to 100% ETc; non-irrigated, but rain fed (NI) and partial root zone drying (PRD) and deficit irrigation (DI), both corresponding to an irrigation of 50% ETc. While in the DI treatment water was applied to both sides of the root system, in the PRD treatment, water was supplied to only one side of the root system, alternating sides periodically. In both cultivars, PRD and DI vines showed intermediate pre-dawn leaf water potential (ψpd) values (around -0.4 MPa) while FI vines, showed ψpd around -0.2 MPa during the growing season. NI showed the lowest cpd, reaching -0.6 MPa in Moscatel and -0.8 MPa in Castelão, at the end of growing season. Water status of PRD vines remained closer to FI than DI, especially at midday. Photosynthetic rates and fluorescence parameters of the deficit irrigation treatments (PRD and DI) did not show significant differences from FI vines, for most of the season. In Moscatel, although PRD generally showed gs, relative stomatal limitation (RSL) and intrinsic water use efficiency (A/gs) values closer to NI than DI, most of the differences between PRD and DI were not statistically significant. Our results showed a stability of the photosynthetic machinery in grapevines under low-to-moderate water availabilities, as demonstrated by the maintenance of the activity of three Calvin Cycle enzymes and of the Vcmax values. However, a decline in Jmax was observed in NI vines, that can be a result either of a decrease in ATP production or, alternatively, of decreased mesophyll conductance to CO2 diffusion. In general terms, stomatal limitation of photosynthesis is likely to be dominant in non-irrigated plants. Deficit irrigation had no negative impact on CO2 assimilation, despite less water application than in full-irrigation. Differences among varieties may be related to differences in sensitivity of stomata, shoot growth and/or the interaction between rootstock and cultivar to soil water availability.